2010
DOI: 10.1016/j.pain.2010.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Cav3.2 T-type calcium channels targeted by endogenous hydrogen sulfide contributes to maintenance of neuropathic pain

Abstract: Hydrogen sulfide (H(2)S) formed from l-cysteine by multiple enzymes including cystathionine-gamma-lyase (CSE) is now considered a gasotransmitter in the mammalian body. Our previous studies have shown that H(2)S activates/sensitizes Ca(v)3.2 T-type Ca(2+) channels, leading to facilitation of somatic and visceral nociception, and that CSE-derived endogenous H(2)S participates in inflammatory pain. Here, we show novel evidence for involvement of the endogenous H(2)S-Ca(v)3.2 pathway in neuropathic pain. In the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
87
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 118 publications
(95 citation statements)
references
References 43 publications
7
87
1
Order By: Relevance
“…Involvement of T-channels in cancer chemotherapy-induced neuropathy was first suggested by a report showing that systemic administration of ethosuximide, a classic T-channel inhibitor, alleviated mechanical and cold allodynia/ hyperalgesia in rats with paclitaxel-or vincristineinduced neuropathy (31). We have confirmed that paclitaxel-induced neuropathic hyperalgesia is abolished by more selective inhibitors of T-channels and by Ca v 3.2 gene silencing, although expression levels of Ca v 3.2 in DRG do not change in this neuropathic pain model (32), differing from the spinal nerve injury-induced neuropathic pain models in which Ca v 3.2 is dramatically upregulated in DRG (28). It is also noteworthy that the paclitaxel-induced neuropathy is reversed by an inhibitor of CSE, suggesting involvement of functional upregulation of the CSE/H 2 S/Ca v 3.2 pathway.…”
Section: Involvement Of T-channels In Neuropathic Painsupporting
confidence: 62%
See 2 more Smart Citations
“…Involvement of T-channels in cancer chemotherapy-induced neuropathy was first suggested by a report showing that systemic administration of ethosuximide, a classic T-channel inhibitor, alleviated mechanical and cold allodynia/ hyperalgesia in rats with paclitaxel-or vincristineinduced neuropathy (31). We have confirmed that paclitaxel-induced neuropathic hyperalgesia is abolished by more selective inhibitors of T-channels and by Ca v 3.2 gene silencing, although expression levels of Ca v 3.2 in DRG do not change in this neuropathic pain model (32), differing from the spinal nerve injury-induced neuropathic pain models in which Ca v 3.2 is dramatically upregulated in DRG (28). It is also noteworthy that the paclitaxel-induced neuropathy is reversed by an inhibitor of CSE, suggesting involvement of functional upregulation of the CSE/H 2 S/Ca v 3.2 pathway.…”
Section: Involvement Of T-channels In Neuropathic Painsupporting
confidence: 62%
“…Interestingly, the neuropathic pain caused by spinal nerve injury is also abolished by two distinct inhibitors of CSE, an H 2 S forming enzyme, suggesting that in addition to the upregulation of Ca v 3.2, sensitization of Ca v 3.2 by CSE-derived endogenous H 2 S through interaction with Zn 2+ , as described in Section 2.1. and shown in Fig. 1, contributes to the neuropathic pain (28). In addition to Ca v 3.2, Ca v 3.1 and Ca v 3.3 may be involved in the pathophysiology of neuropathic pain, considering evidence that neuropathic pain induced by L5 spinal nerve ligation is attenuated in Ca v 3.1-defective mice (29) and that Ca v 3.3, as well as Ca v 3.2, is upregulated at mRNA levels in the spinal cord of the rats with neuropathy induced by chronic compression of DRG (30).…”
Section: Involvement Of T-channels In Neuropathic Painmentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, mibefradil suppressed the phosphorylation of ERK induced by the infusion of NaHS, a pronociceptive stimulus in the pancreatic duct, albeit at higher concentrations than those reported above (500 nM/rat) [46]. Finally, the neuropathic allodynia/hyperalgesia induced in rats by damaging the right L5 spinal nerve [47] or by systemic injection of paclitaxel [48], an anticancer drug, was strongly attenuated by either mibefradil or CSE inhibitors, or by antisense ODNs against rat CaV3.2. In addition, CaV3.2 was significantly up-regulated in the ipsilateral L4, L5, and L6 dorsal root ganglia of rats subjected to spinal nerve injury, but not treated with paclitaxel [48].…”
Section: Calcium Vocsmentioning
confidence: 74%
“…Conversely, reduction of H 2 S reduced the tactile allodynia developed in course of diabetes. The T-type voltage-gated calcium channel Ca V 3.2 is sensitized by H 2 S, leading to increased pain sensitivity (101). An increased H 2 S tissue content and hyperactivity (102).…”
Section: Neuropathymentioning
confidence: 99%